2009
DOI: 10.1021/ol902061j
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Indoles and Aniline Derivatives from Nitroarenes under Hydrogenation Condition with Supported Gold Nanoparticles

Abstract: One-pot sequences of hydrogenation/hydroamination to form indoles from (2-nitroaryl)alkynes and hydrogenation/reductive amination to form aniline derivatives from nitroarenes and aldehydes were catalyzed by Au nanoparticles supported on Fe(2)O(3). Nitro group selective hydrogenations and successive reactions were efficiently catalyzed under the conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 29 publications
(9 reference statements)
1
77
0
Order By: Relevance
“…In contrast to this proposal, we found that acid-base properties of non-reducible oxide support play an important role in H2 dissociation as well as the preferential adsorption of substituted nitroaromatics through the nitro group on the catalyst. Recently, several research groups reported a one-pot procedure for reductive monoalkylation of nitroaromatics using carbonyl compounds as alkyl-source and reducing agents such as H2 106) . In this system, hydrogenation of nitroaromatics and the reductive N-alkylation of aromatic amines with carbonyl compounds proceed in one reactor.…”
Section: Selective Hydrogenation Of Nitroaromaticsmentioning
confidence: 99%
“…In contrast to this proposal, we found that acid-base properties of non-reducible oxide support play an important role in H2 dissociation as well as the preferential adsorption of substituted nitroaromatics through the nitro group on the catalyst. Recently, several research groups reported a one-pot procedure for reductive monoalkylation of nitroaromatics using carbonyl compounds as alkyl-source and reducing agents such as H2 106) . In this system, hydrogenation of nitroaromatics and the reductive N-alkylation of aromatic amines with carbonyl compounds proceed in one reactor.…”
Section: Selective Hydrogenation Of Nitroaromaticsmentioning
confidence: 99%
“…[7] However, the reductive nature of those conditions limited the reaction scope and precluded the possibility of further cascade functionalization. Soon after, Somorjai, Toste, and co-workers reported that Pt nanoparticles supported on mesoporous silica are able to efficiently promote the intramolecular heterocyclization of N-carbamate protected 2-alkynylanilines to afford the corresponding indole products in excellent yields.…”
mentioning
confidence: 99%
“…The use 50 of N- (2,4-dimethoxybenzene) or N-TMS substituted imines allowed access to NH aziridines in good yield on large scale. Scheme 5 55 The use of the N-amino-tetrahydrophthalimide shown in Scheme 6 in the oxidative aminoaziridation of alkenes was found to give excellent yields of trans-aziridines from trans-alkenes, whereas lower reactivity was observed with cis-alkenes. 6 This reaction is believed to proceed via an intermediate aminonitrene which arises from the action of the PhI(OAc) 2 in Scheme 7, the first time that such a process has been observed (previous reactions of azides with enol ethers proceed via 1,3-dipolar cycloaddition).…”
Section: Methodsmentioning
confidence: 99%
“…[51][52][53][54][55][56] Cacchi's 295 approach uses a copper-catalysed C-H functionalisation of readily available N-aryl enaminones. 51 Doyle 52 has shown that intramolecular nucleophilic attack of imines by aryldiazoacetates is catalysed by Lewis acids, facilitating the formation of 2,3-disubstituted indoles in quantitative yields.…”
Section: Scheme 28mentioning
confidence: 99%
See 1 more Smart Citation